Potensi Asap Cair Tandan Kosong Kelapa Sawit Untuk Menekan Pertumbuhan Gulma Teki (Cyperus kyllingia) - Khairunida, Khairunida; Soedijo, Samharinto; ., Salamiah (www.ulm.ac.id, 2024)
C. kyllingia is an annual weed that can cause problems because it can reduce the quantity and quality of cultivated plant production, so this weed needs to be controlled. Weed control with synthetic herbicides is currently more popular because its effectiveness can be seen more quickly. However, if synthetic herbicides are used for a long period of time, they will affect soil conditions. Therefore, an alternative weed control using liquid smoke from empty oil palm fruit bunches (TKKS) is needed. The research aims to determine the potential of TKKS liquid smoke in controlling the growth of sedge weed (C. kyllingia). The design used a 1 factor Completely Randomized Design consisting of 5 treatments and 5 replications with liquid smoke concentrations of 0%, 8.3%, 16.6%, 25% and 33.3%. Research shows that TKKS liquid smoke has the potential to be used as a natural herbicide because it has an effect on suppressing the growth of the C. kyllingia weed. The best concentration that can suppress weed growth is 33.3% liquid smoke.